(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Urban green spaces and public parks are vital for enhancing environmental quality, public health, and community well being. This study investigates the role of local governments in managing these spaces and their contribution to improving urban quality of life. A mixed methods approach was employed, combining structured interviews, GIS based spatial analysis, and statistical correlation between green space indicators and quality of l ife measures. The results indicate that municipalities with proactive governance, participatory planning, and consistent maintenance achieve higher biodiversity, greater accessibility, and increased citizen satisfaction. Case comparisons revealed that citi es investing more resources in green space management recorded higher visitor numbers and better public feedback. The study underscores that effective local governance is essential in fostering sustainable and inclusive urban environments, linking environm ental conservation with social and recreational needs.